2003
DOI: 10.1021/ic020611n
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cleavage of DNA by a New Ferromagnetic Linear Trinuclear Copper(II) Complex in the Presence of H2O2/Sodium Ascorbate

Abstract: A new trinuclear copper(II) complex has been synthesized and structurally characterized: [Cu(3)(L)(2)(HCOO)(2)(OH)(2)](infinity) (HL = (N-pyrid-2-ylmethyl)benzenesulfonylamide). In the complex, the central copper ion is six-coordinated. The coordination spheres of the terminal copper atoms are square pyramidal, the apical positions being occupied by a sulfonamido oxygen of the contiguous trimer. As a consequence, the complex can be considered a chain of trinuclear species. The three copper atoms are in a stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 20 publications
2
56
1
Order By: Relevance
“…The strong CL phenomenon indicated that ROS was released on CaO 2 . In order to acquire sufficient evidence, ascorbic acid, a well-known ROS scavenger (22)(23)(24), was chosen for further experiments. As shown in Fig.…”
Section: Confirmation Of Ros On Cao 2 By CLmentioning
confidence: 99%
“…The strong CL phenomenon indicated that ROS was released on CaO 2 . In order to acquire sufficient evidence, ascorbic acid, a well-known ROS scavenger (22)(23)(24), was chosen for further experiments. As shown in Fig.…”
Section: Confirmation Of Ros On Cao 2 By CLmentioning
confidence: 99%
“…Although to date remarkable Cu(I) complexes [8][9][10][11] and examples of Cu(I) complexes with halocuprate anion [12][13][14] have been reported, there is no report on diiodocuprate (I) anion polymeric complex with ethylenediamine. Thus, we report herein the electrosynthesis and crystal structure of a novel Cu(I) polymeric complex with potentiostatic dissolution of copper anode in a solution of ethylendiamine and iodine in AcN.…”
Section: Introductionmentioning
confidence: 99%
“…4) [18,38]. The DNA cleavage was obviously inhibited after the addition of NaN 3 (lane 3) or superoxide dismutase SOD (lane 4), which suggests that singlet oxygen ( 1 O 2 ) and the superoxide radical (O 2 -) are responsible for strand scission.…”
Section: Plasmid Puc19 Dna Cleavage In the Presence Of Standard Radicmentioning
confidence: 96%